The Origins of P Literary Profiles and Strata of the Priestly Texts in Genesis 1 - Exodus 40 - Hutzli, Jürg (Mohr Siebeck, 2023)
In this study, Jürg Hutzli analyses all Priestly texts in Genesis-Exodus. He evaluates crucial questions concerning P, namely inner stratification, literary profile, historical setting, and relationship to the non-P "environment" separately for each Priestly unit or section. An important result of the author's study is the conclusion that the Priestly texts form a stratum that is more composite and less homogeneous than previously thought. Single units like Gen. 1, the Priestly flood story, and the Priestly Abraham narrative have their own distinct theologies that do not fit that of the comprehensive Priestly composition in every respect. Furthermore, as recent studies point out, the literary profile of P is not the same in every section (either a source or a redaction). The author evaluates these observations diachronically for an inner differentiation of the Priestly strand.